2019
DOI: 10.1038/s41598-019-50615-0
|View full text |Cite
|
Sign up to set email alerts
|

Reducing EphA4 before disease onset does not affect survival in a mouse model of Amyotrophic Lateral Sclerosis

Abstract: Amyotrophic lateral sclerosis (ALS) is a neurodegenerative disease that affects motor neurons resulting in severe neurological symptoms. Previous findings of our lab suggested that the axonal guidance tyrosine-kinase receptor EphA4 is an ALS disease-modifying gene. Reduction of EphA4 from developmental stages onwards rescued a motor neuron phenotype in zebrafish, and heterozygous deletion before birth in the SOD1G93A mouse model of ALS resulted in improved survival. Here, we aimed to gain more insights in the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
6
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 30 publications
1
6
0
Order By: Relevance
“…Despite limitations with the SOD1 G93A model, our results raise significant doubts about the therapeutic hypothesis that reducing EphA4 is beneficial. Our failure to observe any benefits of EphA4 KO in grip strength, CMAP amplitude, NMJ denervation or motor neuron loss phenotypes, and worsening of some of these phenotypes in the SOD1 G93A model is consistent with other studies that failed to see benefits of postnatal reduction of EphA4 levels with antisense oligonucleotides 9 or with inducible global or motoneuron EphA4 KO 10 . One potential limitation of our study is that we did not perform survival analysis.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…Despite limitations with the SOD1 G93A model, our results raise significant doubts about the therapeutic hypothesis that reducing EphA4 is beneficial. Our failure to observe any benefits of EphA4 KO in grip strength, CMAP amplitude, NMJ denervation or motor neuron loss phenotypes, and worsening of some of these phenotypes in the SOD1 G93A model is consistent with other studies that failed to see benefits of postnatal reduction of EphA4 levels with antisense oligonucleotides 9 or with inducible global or motoneuron EphA4 KO 10 . One potential limitation of our study is that we did not perform survival analysis.…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, a different study found that CNS reduction of EphA4 levels with antisense oligonucleotides delivered directly to the central nervous system starting at 49 days of age had no benefit for motor function or survival in two ALS models, including SOD1 G93A mice 9 . Similarly, recent work using inducible KO of EphA4 found that reduction of global EphA4 or motoneuron EphA4 starting at 60 days of age did not modify disease course or improve survival in SOD1 G93A mice 10 .…”
mentioning
confidence: 83%
“…Epha4-specific nanobodies [39], an EphA4 receptor soluble antagonist [40] and selective Epha4-binding compounds [41], were developed to treat ALS and delivered encouraging results in delaying disease progression in the SOD1 G93A model. However, pre-symptomatic lowering of Epha4 levels in ALS mice, ubiquitously or specifically in CNS, by genetic abrogation or by administration of antisense oligonucleotides (ASOs) did not show a significant improvement in motor function, disease onset, or survival [42,43]. This probably reflects a highly complex mechanism of Epha4, or the ephrin system in general, in ALS pathogenic processes [14].…”
Section: Eph Receptors (Ephrin Receptor Family)mentioning
confidence: 99%
“…While deletion of the EphA4 gene (heterozygous) in a SOD1(G93A) mouse model of ALS resulted in improved survival, 1 more recent studies seemed to be contradictory on how and when to target EphA4 in ALS. For example, ubiquitous reduction of EphA4 levels to 50% in the same SOD1(G93A) mice at 60 days of age did not improve disease onset or survival, 11 suggesting that specific knockdown in EphA4 in adulthood may have a limited therapeutic potential for ALS. Moreover, pharmacological inhibition of EphA4 also produced nonconclusive results using transgenic SOD1-(G93A) animal models.…”
Section: ■ Introductionmentioning
confidence: 99%